Transmission of obliquely incident surface waves through a narrow gap - B. N. Mandal; P. K. Kundu (International Journal of Mathematics and Mathematical Sciences)
This note is concerned with the transmission of a train of surface water waves obliquely incident on a thin plane vertical barrier with a narrow gap. Within the framework of the linearized theory of water waves, the problem is reduced to the solution of an integral equation which is solved approximately. The transmission and reflection co–efficients are also obtained approximately and represented graphically against the different angles of incidence for fixed wave numbers.